2007
DOI: 10.1243/09544070jauto458
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of the dual-fuel performance of a small compression ignition diesel engine operating with three gaseous fuels

Abstract: Abstract:A dual-fuel engine is a compression ignition (CI) engine where the primary gaseous fuel source is premixed with air as it enters the combustion chamber. This homogenous mixture is ignited by a small quantity of diesel, the 'pilot', that is injected towards the end of the compression stroke. In the present study, a direct-injection CI engine, was fuelled with three different gaseous fuels: methane, propane, and butane. The engine performance at various gaseous concentrations was recorded at 1500 r/min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…NO X is strongly dependent on local temperatures so most NO X is expected to form in the region around the pilot spray where high temperatures exist and the equivalence ratio is close to stoichiometric [17]. Earlier and faster combustion events increase the duration for which in-cylinder conditions are suitable for NO X formation [18].…”
Section: Introductionmentioning
confidence: 99%
“…NO X is strongly dependent on local temperatures so most NO X is expected to form in the region around the pilot spray where high temperatures exist and the equivalence ratio is close to stoichiometric [17]. Earlier and faster combustion events increase the duration for which in-cylinder conditions are suitable for NO X formation [18].…”
Section: Introductionmentioning
confidence: 99%
“…An injector driver circuit was built and used to control the opening and closing of the injector valve by which we were able to control the injection timing and injection duration which was built into a lab VIEW program. In order to study a single fuel spray, different researchers modified their injectors from different numbers of holes to study a single-hole nozzle [3]- [5], [9]. D. A. Kennaird et al [17] in their study of multi-hole and single hole injectors spray penetration characteristics found that, single-hole injector was valid to characterize spray.…”
Section: A Experimental Test Rigmentioning
confidence: 99%
“…This kind of operating condition produces a none-uniform mixture distribution of the natural gas inside the engine. In addition, this system does not favor the two-stroke engine due to the escape of some of the natural gas fuel into the exhaust [3]. The second method of using natural gas in diesel engines is the direct injection of natural gas near to the diesel fuel spray into the combustion chamber [4].…”
Section: Introductionmentioning
confidence: 99%
“…While soot content in the exhaust has historically been regulated on a gravimetric basis, there also exists a concern about particle size; fine particle concentration, for instance, has been shown to cause adverse health effects [3]. Assuming a mean "spherical" diameter, particles in the 100-300 nm diameter range constitute the accumulation mode, while nucleation mode particles are typically 5-50 nm in diameter [4], Dual-fueling strategies have been pursued to improve engineout exhaust emissions while maintaining diesel-like fuel conver sion efficiencies at some loads (5,6]. Contributed by the Combustion and Fuels Committee of ASME for publication in the Journal of E ngineering for G as T urbines and P ower.…”
Section: Introductionmentioning
confidence: 99%